Polyamide composite membrane
By optimizing the functional group content and network structure of the polyamide separation layer, the problem of low efficiency of existing reverse osmosis membranes in the process of boron -destruction process is solved. Essence
Patent Information
- Application Number
- CN202411471321.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-28
AI Technical Summary
The existing reverse osmosis membranes are inefficient in the deboring process and have poor retention of boric acid in acidic and neutral aqueous solutions, resulting in low deboring rate.
The functional group content of the infrared appearance is optimized to optimize the separation layer of the polyamide, and the polyamide separation layer is formed through the interface to reduce its network structure and polarity to improve the boron -dehydration and alkali resistance.
While maintaining the high -throughput and high -junctive salt rate, it improves the decapyllar performance of the membrane and the stability of alkali resistance, and is suitable for the field of water treatment and other water treatment fields.
Smart Images

Figure BDA0005094777570000061 
Figure BDA0005094777570000062 
Figure BDA0005094777570000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of separation membranes, and in particular relates to a polyamide composite membrane. Background Art
[0002] Separation membrane is a technology that uses physical separation methods to treat water. Polyamide composite membrane can effectively intercept ions in water and allow water to pass through. It is widely used in brackish water desalination, reclaimed water reuse, seawater desalination and other fields.
[0003] Most of the boron exists in water in the form of boric acid molecules, and its molecular size is extremely small, so conventional reverse osmosis membranes have a poor retention effect on boron. The main reasons for the low boron removal rate of reverse osmosis membranes are: (1) In acidic and neutral aqueous solutions, boric acid mainly exists in the form of uncharged boric acid molecules, which makes the charge repulsion mechanism of the reverse osmosis membrane ineffective; (2) The molecular radius of boric acid is smaller than most aggregate pores and some mesh pores;
[0004] (3) The transfer mode of boric acid in the membrane is very similar to that of water (H2O).
[0005] At present, industrial water treatment mainly improves the boron retention rate through multi-stage reverse osmosis, reverse osmosis and adsorption resin, and improved pretreatment, but the cost increases. The core of reverse osmosis technology is high-performance reverse osmosis membrane, so the preparation of reverse osmosis membrane with high boron removal performance can improve the boron removal effect from the source.
[0006] There are two main methods to improve the boron removal rate of reverse osmosis membranes: (1) reducing the chemical polarity of the reverse osmosis membrane polyamide and reducing the hydrogen bonding force between the polyamide and boric acid molecules; (2) reducing the pore size of the reverse osmosis membrane and improving the physical screening effect.
[0007] Shultz et al. swelled polyamide with alcohol and then embedded hydrophobic fatty amine into the membrane pores, thereby increasing the deboronization rate by reducing polarity and shrinking pore size; Zhang and Raval et al. synthesized sulfonated diamine to replace m-phenylenediamine, and used sulfonic acid groups to fill the membrane pores, thereby increasing the deboronization rate; Patent CN100379488C used a mixed aqueous solution of monoamine and polyamine as the aqueous phase, and after reacting with fatty acid chlorides, it was treated with sodium hypochlorite to produce a high deboronization reverse osmosis membrane.
[0008] Although some technical solutions for preparing polyamide reverse osmosis membranes with high boron removal rates have been formed in the prior art, the prior art solutions are still not mature enough or still need to be further improved. Summary of the invention
[0009] The purpose of the present invention is to provide a polyamide composite membrane in view of the shortcomings of the prior art. The polyamide composite membrane provided by the present invention can improve the boron removal performance of the membrane and the stability after alkali resistance while maintaining high flux and high salt rejection. The polyamide composite membrane of the present invention can be used in water treatment fields such as seawater desalination.
[0010] In order to achieve the above object, the present invention adopts the following technical solution:
[0011] The present invention provides a polyamide composite membrane, which comprises a substrate, a base membrane and a polyamide separation layer formed on a porous support layer. The polyamide separation layer is characterized by infrared at 1663 cm -1 The characteristic peak of amide is red-shifted to the low wave number band by 1-13 cm -1 .
[0012] Specifically, the infrared spectrum at 1663 cm -1 The amide absorption peak is attributed to the stretching vibration of C=O of amide.
[0013] The applicant has found through research that the content of functional groups (such as amino and carboxyl groups) in the polyamide separation layer is closely related to the deboronization rate. Due to the change in the content of functional groups in the polyamide separation layer, the polarity and network structure of the polyamide network change, resulting in the infrared spectrum at 1663cm -1 The C=O characteristic peak of amide produces red shift or blue shift. The applicant found that when the infrared spectrum is at 1663cm -1 The C=O characteristic peak of amide is red-shifted by 1-13 cm -1 When the red shift of the C=O characteristic peak of amide is greater than 13 cm -1 Therefore, in order to ensure that the polyamide composite membrane prepared by the present invention maintains a high flux, the present invention preferably uses an infrared spectrum at 1663cm -1 The C=O characteristic peak of amide is red-shifted by 1-13 cm -1 , for example 1cm -1 , 3cm -1 , 5cm -1 、8cm -1 , 10cm -1 、12cm -1 、13cm -1 , preferably red shift 1-5cm -1 .
[0014] Preferably, the polyamide separation layer of the present invention is characterized by Zeta potential, and under the measurement conditions of pH=6 and 1 mM potassium chloride, the surface potential is -10 mV to -35 mV.
[0015] The applicant has found that changes in the content of some unreacted amino and carboxyl functional groups in the polyamide network will also affect the potential of the membrane surface. In order to maintain the water permeability and salt rejection rate of the composite membrane, the present invention preferably has a surface potential of -10mV to -35mV under the measurement conditions of PH = 6 and 1mM potassium chloride, for example, -35mV, -32mV, -30mV, -25mV, -23mV, -20mV, -18mV, -15mV, -12mV, -10mV, preferably -28mV to -33mV.
[0016] It should be noted that the infrared characterization described in the present invention is measured by total reflection infrared spectroscopy (ATR), and the Zeta potential is measured by an electric solid surface analyzer. The specific test conditions are described in the specific examples.
[0017] The substrate of the present invention is selected from polyester non-woven fabric, with a thickness of 70-110um and a preferred air permeability of 0.5-2.5cm 3 / cm 2 / s.
[0018] The base membrane of the present invention has a thickness of 30-50um and a surface pore size of 10-50nm. Its raw material is selected from one or more of polysulfone membrane, polyethersulfone membrane, polyamide membrane, polyester membrane, polyphenylene sulfide membrane, polyphenylsulfone membrane, polyphenylene sulfide sulfone membrane, polyphenylene ether membrane, etc., preferably polysulfone membrane.
[0019] The polyamide separation layer is formed by interfacial polycondensation of an aqueous solution containing a polyfunctional amine and an organic solution containing a polyfunctional acid halide on the surface of the base film.
[0020] The following is an explanation of the method for preparing the separation layer of the polyamide composite membrane. The multifunctional amine is selected from at least one of aromatic multifunctional amines and aliphatic multifunctional amines.
[0021] The aromatic multifunctional amine is an aromatic amine having two or more amino groups in one molecule, and is not particularly limited, and can be selected from one or more of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, 2,4-diaminotoluene, 2,6-diaminotoluene, 1,3,5-triaminobenzene, etc.; preferably one or more of m-phenylenediamine and 1,3,5-triaminobenzene;
[0022] The aliphatic multifunctional amine is an aliphatic amine having two or more amino groups in one molecule, and is not particularly limited, and can be selected from one or more of piperazine, 4-aminomethylpiperazine, 2,5-dimethylpiperazine, ethylenediamine, hexamethylenediamine, dimethyldiamine, diethylenetriamine, triethylenetetramine, 1,3-diaminocyclohexane, 1,2-diaminocyclohexane, polyethyleneimine, etc.; preferably one or more of ethylenediamine, propylenediamine, and piperazine.
[0023] Further, the concentration of the multifunctional amine in the aqueous solution is 1-10wt.%, preferably 2-6wt.%;
[0024] The polyfunctional acyl halide can be selected from acyl halides having two or more halogenated carbonyl groups in one molecule, as long as it can react with the above-mentioned polyfunctional amines to form polyamide. Among the acyl halides, acyl chlorides are preferred, such as one or more selected from trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and adipoyl chloride; trimesoyl chloride is more preferred.
[0025] The organic solvent in the organic phase solution for dissolving the polyfunctional acyl halide is selected from non-polar solvents, such as one or more of n-hexane, cyclohexane, n-heptane, n-decane, Isopar L isoparaffin and Isopar G isoparaffin, preferably Isopar G.
[0026] The concentration of the polyfunctional acyl halide in the organic phase solution is 0.05-0.3 wt.%, preferably 0.1-0.25 wt.%;
[0027] The interfacial polymerization reaction has a reaction temperature of room temperature, preferably 20-25° C., and a reaction time of 2-60 s, preferably 5-15 s;
[0028] After the interfacial polymerization, the excess organic phase is removed. The excess organic phase can be removed by oven, infrared heating, solvent washing and other methods. The oven method is preferred. The oven temperature is preferably 40-60° C. and the treatment time is 30-120 s.
[0029] In the aqueous solution of the multifunctional amine, auxiliary agents such as surfactants and acid-binding agents may be added as needed, such as sodium dodecyl sulfate and sodium dodecylbenzene sulfonate, and acid-binding agents such as sodium bicarbonate and triethylamine. The mass concentration of the surfactant in the aqueous solution is preferably 0.001-0.1wt.%; the mass concentration of the acid-binding agent in the aqueous solution is preferably 0.01-0.2wt.%.
[0030] Methods for controlling the content of functional groups such as carboxyl and amino groups in the polyamide separation layer include: adding functional monomers or additives to the aqueous phase or organic phase when forming the separation functional layer; adjusting by heat treatment or other processes when forming the separation functional layer; and adjusting by post-treatment after forming the separation functional layer. A combination of the above methods may also be used.
[0031] The method for controlling the functional group content, especially the carboxyl content, of the separation layer of the polyamide composite membrane is described as follows:
[0032] In a specific embodiment, for example, a long carbon chain phase transfer catalyst is added to the aqueous phase, preferably with 12-16 carbon atoms, and preferably the long carbon chain phase transfer catalyst contains a functional group such as ammonium chloride or ammonium bromide, such as dodecylbenzyldimethylammonium bromide, dodecylbenzyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride, etc.
[0033] The long carbon chain phase transfer catalyst can not only catalyze the reaction between amine and acyl chloride, but the long carbon chain can also change the stability of the interface, promote the diffusion of amine, increase the degree of crosslinking, and reduce carboxyl end-capping. At the same time, the obtained polyamide separation layer is post-treated by mixing nitrite (such as sodium nitrite, potassium nitrite) and inorganic acid (such as hydrochloric acid, sulfuric acid, phosphoric acid) and then contacting to improve the hydrophilicity of the membrane to obtain a polyamide composite membrane.
[0034] Specifically, the concentration of the long carbon chain phase transfer catalyst in the aqueous solution is 0.001wt.%-0.02wt.%;
[0035] Specifically, the nitrite concentration is preferably 0.05wt.%-0.5wt.%, the pH of the nitrite after mixing with the inorganic acid is 2-4, the post-treatment temperature is preferably 15-35°C, and the post-treatment contact time is preferably 10-120s.
[0036] In another specific embodiment, for example, amino acid benzyl ester p-toluenesulfonate is added to the aqueous phase.
[0037] Specifically, the amino acid benzyl ester p-toluenesulfonate can be selected from one or more of β-alanine benzyl ester p-toluenesulfonate, L-tyrosine benzyl ester p-toluenesulfonate, and glycine benzyl ester p-toluenesulfonate, preferably glycine benzyl ester p-toluenesulfonate.
[0038] Specifically, the concentration of the amino acid benzyl ester p-toluenesulfonate in the aqueous solution is 0.01-0.5 wt.%, preferably 0.05-0.2 wt.%.
[0039] The benzyl ester end of amino acid benzyl ester has a certain affinity with oil and can diffuse into the organic phase during the interfacial polymerization process. The primary amine in the amino acid reacts with the acyl chloride, so that the amino acid benzyl ester is interspersed in the polyamide network. The generated amide benzyl ester has a certain hydrophobicity at the benzyl ester end, which not only affects the formation of hydrogen bonds between polyamide chains, increasing the space between polyamide chains, but also forms a certain micro-hydrophobic area in the polyamide network, reducing the hydrogen bonding effect between water and water during water transmission, which is beneficial to water penetration; the formed micro-hydrophobic area reduces the polarity of polyamide and improves the retention of boron. At the same time, the added amino acid benzyl ester p-toluenesulfonate affects the formation of carboxyl groups in the polyamide network, reduces the carboxyl content, reduces the polarity of polyamide, and improves the retention of boron.
[0040] The polyamide composite membrane of the present invention is used in the fields of reclaimed water reuse, seawater desalination, brackish water desalination, etc.
[0041] Compared with the prior art, the polyamide composite membrane of the present invention has the properties of high flux, salt rejection rate, boron removal rate and alkali resistance. DETAILED DESCRIPTION
[0042] The following specific embodiments are further explanations of the technical solutions provided by the present invention, but should not be construed as limitations of the present invention.
[0043] Membrane performance test:
[0044] 1. Evaluation of water flux, desalination rate and boron removal rate:
[0045] Water flux and desalination rate test method: refer to the water flux and desalination rate test method in GB / T32373-2015 "Reverse Osmosis Membrane Test Method".
[0046] The boron removal rate (Rb) is defined as: under certain operating conditions, the difference between the boron concentration in the feed solution and the boron concentration in the permeate, divided by the boron concentration in the feed solution (the boron concentration in the solution is characterized by the ICP method).
[0047] The operating conditions used in the polyamide reverse osmosis composite membrane performance measurement in the present invention are: the inlet liquid is 32000ppm sodium chloride aqueous solution, the boron content is 5ppm, the operating pressure is 5.5MPa, the operating temperature is 25°C, and the pH of the aqueous solution is 8.
[0048] 2. Alkali resistance evaluation:
[0049] The membrane was immersed in a 25°C sodium hydroxide solution with a pH of 13 for 16 hours, and then taken out and rinsed with pure water to test the performance of the membrane.
[0050] 3. Infrared characterization: measured by total reflection infrared spectroscopy (ATR). The test instrument used was FTIR-650 produced by Tianjin Gangdong Technology Co., Ltd.
[0051] 4. Zeta potential characterization: The test instrument used was Anton Paar SurPASS, and the test was conducted under the conditions of pH=6 and 1 mM potassium chloride.
[0052] 5. Source of raw materials:
[0053] Amino acid benzyl ester p-toluenesulfonate: Aladdin;
[0054] The polyester nonwoven fabric substrate was purchased from Mitsubishi Paper Co., Ltd., with a thickness of 80 μm and an air permeability of 2 cm 3 / cm 2 / s;
[0055] Polysulfone: Solvay P3500 LCD MB7.
[0056] The polysulfone membrane supported by the nonwoven fabric described in the examples was prepared by referring to the method mentioned in CN114053886A.
[0057] Examples 1 to 3
[0058] (1) Preparation of aqueous solution: m-phenylenediamine, glycine benzyl p-toluenesulfonate, sodium dodecylbenzenesulfonate, triethylamine and water are uniformly mixed to obtain an aqueous solution; wherein the concentration of substances in the aqueous solution is shown in Table 1;
[0059] (2) Preparation of oil phase solution: dissolving trimesoyl chloride in isoparG and stirring to obtain an oil phase solution, wherein the concentration of trimesoyl chloride in the oil phase solution is 0.14 wt %;
[0060] (3) Interfacial polymerization and post-treatment: The polysulfone membrane (thickness 40 μm, surface pore size 40 nm) supported by the non-woven fabric is directly immersed in the aqueous solution prepared in step (1) for 30 seconds. After being taken out, it is squeezed with a rubber roller to remove the excess aqueous solution on the surface of the polysulfone membrane. It is then immersed in the oil solution prepared in step (2) to react at room temperature for 10 seconds. After being taken out, it is placed in a 50°C oven for reaction for 1 minute. After being taken out, it is cleaned with pure water to obtain a polyamide composite membrane.
[0061] Comparative Example 1
[0062] Referring to Example 2, the preparation method is different from that of Example 2 in that: glycine benzyl ester p-toluenesulfonate is not added to the aqueous phase.
[0063] Table 1 Composition of aqueous solutions of Examples 1-3 and Comparative Example 1
[0064]
[0065] The polyamide reverse osmosis membranes prepared according to Examples 1 to 3 and Comparative Example 1 were subjected to infrared characterization and separation performance tests. The analysis and test results are shown in Table 2.
[0066] Table 2 Performance test of polyamide composite membranes of Examples 1-3 and Comparative Examples
[0067]
[0068]
[0069] Example 4
[0070] Referring to Example 1, the main difference between this example and Example 1 is that the concentration of trimesoyl chloride in the oil phase is 0.2wt.%, and glycine benzyl p-toluenesulfonate in the aqueous phase is changed to L-tyrosine benzyl p-toluenesulfonate, with a concentration of 0.05wt.%.
[0071] Example 5
[0072] Referring to Example 1, the preparation method is different from that of Example 1 in that the content of sodium dodecylbenzenesulfonate in the aqueous phase is 0.08 wt.%, and the content of triethylamine is 0.18 wt.%.
[0073] Example 6
[0074] Referring to Example 1, the preparation method is different from that of Example 1 in that 0.01 wt.% adipoyl chloride is additionally added to the oil phase, and the oven temperature is set at 60° C. for 1 min.
[0075] Comparative Example 2
[0076] Referring to Example 6, the preparation method is different from that of Example 6 in that: 0.15 wt. % of adipoyl chloride and 0.2 wt. % of trimesoyl chloride are added instead of 0.14 wt. % of trimesoyl chloride and 0.01 wt. % of adipoyl chloride in the oil phase, and the oven temperature is 65° C. for reaction for 1 min.
[0077] The polyamide reverse osmosis membranes prepared according to Examples 4 to 6 and Comparative Example 2 were subjected to separation performance tests and infrared standards. The test and characterization results are shown in Table 3.
[0078] Table 3 Performance test of polyamide composite membrane of Examples 4-6 and Comparative Example 2
[0079]
[0080] Example 7
[0081] 4wt% m-phenylenediamine, 0.01wt.% dodecylbenzyldimethylammonium bromide and pure water were prepared into an aqueous phase, and then the base film was immersed in the aqueous phase for 1 min. After being taken out, the excess aqueous phase on the surface was removed with a rubber roller, and then placed in an oil phase prepared with 0.12wt.% trimesoyl chloride and cyclohexane, and reacted for 1 min. After being taken out, it was placed in a 50°C oven for 30s. After the reaction, it was washed in 90°C hot water for 3 min, and then placed in 0.2wt.% sodium nitrite solution with PH=3 adjusted by 25°C sulfuric acid, post-treated for 1 min, and washed in 90°C hot water for 3 min after being taken out.
[0082] Example 8
[0083] Referring to Example 7, the preparation method is different from that of Example 7 in that the long carbon chain phase transfer catalyst added to the aqueous phase is hexadecyl dimethyl benzyl ammonium chloride, and the concentration is 0.005 wt.%.
[0084] Example 9
[0085] Referring to Example 7, the preparation method is different from that of Example 7 in that the temperature of the sodium nitrite treatment is 35° C. and the pH is 2.
[0086] Comparative Example 3
[0087] Referring to Example 7, the preparation method is different from that of Example 7 in that dodecylbenzyldimethylammonium bromide is not added to the aqueous phase.
[0088] Comparative Example 4
[0089] Referring to Example 7, the preparation method is different from that of Example 7 in that the sodium nitrite post-treatment process is not performed.
[0090] Table 4 Performance test of polyamide composite membranes of Examples 7-9 and Comparative Examples 3-4
[0091]
Claims
1. A polyamide composite membrane, characterized in that: The invention comprises a substrate, a base membrane and a polyamide separation layer formed on a porous support layer, wherein the polyamide separation layer is characterized by infrared at 1663 cm -1 The characteristic peak of amide is red-shifted to the low wave number band by 1-13 cm -1 .
2. The polyamide composite membrane according to claim 1, characterized in that The polyamide separation layer is characterized by Zeta potential. Under the measurement conditions of pH=6 and 1 mM potassium chloride, the surface Zeta potential is -10 mV to -35 mV.
3. The polyamide composite membrane according to claim 1 or 2, characterized in that: The substrate is selected from polyester non-woven fabric with a thickness of 70-110um and an air permeability of 0.5-2.5cm 3 / cm 2 / s.
4. The polyamide composite membrane according to claim 1 or 2, characterized in that: The base membrane has a thickness of 30-50um and a surface pore size of 10-50nm, and its raw material is selected from one or more of polysulfone membrane, polyethersulfone membrane, polyamide membrane, polyester membrane, polyphenylene sulfide membrane, polyphenylene sulfone membrane, polyphenylene sulfide sulfone membrane, and polyphenylene ether membrane.
5. The polyamide composite membrane according to claim 1 or 2, characterized in that: The polyamide separation layer is obtained by interfacial polymerization of an aqueous solution containing multifunctional amines and an organic solution containing multifunctional acyl halides on the surface of a base film.
6. The polyamide composite membrane according to claim 5, characterized in that: The multifunctional amine is selected from one or more of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, 2,4-diaminotoluene, 2,6-diaminotoluene, 1,3,5-triaminobenzene, piperazine, 4-aminomethylpiperazine, 2,5-dimethylpiperazine, ethylenediamine, hexamethylenediamine, dimethyldiamine, diethylenetriamine, triethylenetetramine, 1,3-diaminocyclohexane, 1,2-diaminocyclohexane, and polyethyleneimine; preferably, the concentration of the multifunctional amine in the aqueous solution is 1-10wt.%.
7. The polyamide composite membrane according to claim 5, characterized in that: The polyfunctional acyl halide is a polyfunctional acyl chloride selected from one or more of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride and adipoyl chloride.
8. The polyamide composite membrane according to claim 5, characterized in that The organic solvent in the organic phase solution is selected from one or more of n-hexane, cyclohexane, n-heptane, n-decane, Isopar L isoparaffin and Isopar G isoparaffin; preferably, the concentration of the multifunctional acyl halide in the organic phase solution is 0.05-0.5wt%.
9. The polyamide composite membrane according to claim 5, characterized in that: The interfacial polymerization reaction temperature is 20-25° C., and the reaction time is 2-60 s.
10. Use of the polyamide composite membrane according to any one of claims 1 to 9 in the fields of reclaimed water reuse, seawater desalination, and brackish water desalination.
Citation Information
Patent Citations
Composite semipermeable membrane, and production process thereof
CN100379488C
Polyamide composite reverse osmosis membrane and preparation method thereof
CN114053886A
Preparation method of chitosan composited N-diphenylmethylene-amino-glycine benzyl ester anticoagulant material
CN105477691A
Polyamide composite reverse osmosis membrane with high selective permeability and antibacterial property and preparation method thereof
CN113477085A
METHOD FOR PRODUCING A COMPOSITE POLYMER MEMBRANE FOR REVERSE OSMOSIS
RU2012108971A